Experimental Study on Mechanical Properties of Novel FRP Bars with Hoop Winding Layer - Yue Liu; Hong-Tao Zhang; Hong-Hao Zhao; Lin Lu; Ming-Yang Han; Jiao-Cai Wang; Shuai Guan (Advances in Materials Science and Engineering)
Due to the fact that steel reinforcement is vulnerable to corrosion, FRP bars with light weight, high strength, and excellent durability have become a good substitute for ordinary steel bars. FRP bars have high tensile strength, but their compressive strength is relatively low and often neglected, so the application of FRP bars in compression members has been restricted. This paper proposes a new pultrusion-winding-pultrusion method to improve the compressive ability of FRP bars. A hoop FRP layer is winded on the outer surface of the pultruded FRP core, and a longitudinal pultruded layer and ribs are also added on the outermost surface. In this paper, mechanical properties of this novel FRP bar with hoop winding layer are investigated. First, monotonic tensile and compressive tests on traditional and novel GFRP bars were conducted. Then, cyclic tension-compression loading tests were also carried out on the two types of GFRP bars. Test results showed that the compressive ultimate bearing capacities of GFRP bars with winding layers were 10∼20 kN greater than those of the traditional GFRP bars, and the compressive ductility of the novel GFRP bars was also improved. Furthermore, the tensile stress-strain behaviors of both GFRP bars were linear-elastic and the added winding layer did not greatly influence the tensile properties of the GFRP bars. Moreover, for the cyclic loading test, the compressive ultimate load of GFRP bars was 80%∼90% of that under monotonic compressive test, and the tensile ultimate load was 45%∼65% of that under monotonic tensile test. Compared with the GFRP bar without winding layer, the overall stiffness of the novel GFRP bar was greater than that of the traditional one and the ultimate load of the novel GFRP bar was also greater. In addition, seeing that the residual displacement of the novel GFRP bar was greater than that of the traditional GFRP bar, winding hoop fibers on the outer surface of the core is a useful way to improve the energy dissipation capacity of the GFRP bar.